Shelf Water Export at the Brazil-Malvinas Confluence Evidenced From Combined in situ and Satellite Observations - Manta, Gaston; Speich, Sabrina; Barreiro, Marcelo; Trinchin, Romina; de Mello, Camila; Laxenaire, Rémi; Piola, Alberto R. (Frontiers in Marine Science, 2022)
The Brazil-Malvinas Confluence (BMC) is the region where opposing and intense western boundary currents meet along the Southwestern Atlantic slope at about 38°S, generating one of the most energetic mesoscale regions of the global ocean. Based on shipborne observations acquired within the Uruguayan Economic Exclusive Zone (EEZ), combined with satellite data and an eddy tracking algorithm, we analyze the cross-shelf exchanges during May 2016, when the BMC was in an anomalous northern position. Two types of shelf water export were observed triggered by mesoscale dynamics: one was the export of shallow Rio de la Plata Plume waters driven off-shelf by the retroflection of the Brazil Current. This export formed a 70 km wide, 20 m deep filament that propagated offshore at 0.3 m s–1, with a transport of 0.42 Sv. It lasted about 10 days before being mixed with ambient Confluence waters by strong winds. An additional type of off-shelf transport consisted of a subsurface layer of Subantarctic Shelf Waters (SASW) about 60 m thick that subducted at the BMC reaching 130 m deep and transporting 0.91 ± 0.91 Sv. We show that geostrophic currents derived from satellite altimetry over the slope can be useful to track this subsurface off-shelf export as they are significantly correlated with absolute velocity measurements at this depth. Argo temperature and salinity profiles show evidence of these two types of shelf water export occurring between the BMC front and the separation of the Brazil Current from the shelf-break, suggesting this is a relatively frequent phenomenon, in agreement with previous observations.